2013
DOI: 10.11622/smedj.2013139
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid improves insulin sensitivity and blood sugar in overweight type 2 diabetes mellitus patients: a double-blind randomised clinical trial

Abstract: MeThODs This double-blind, placebo-controlled randomised clinical trial was conducted on a total of 67 overweight patients with T2DM for a duration of three months. Of these 67 patients, 32 received 2 g purified EPA daily, while 35 received a placebo of 2 g corn oil daily. The patients' fasting plasma glucose (FPG), serum insulin, glycated haemoglobin (HbA1c) and insulin sensitivity indices were assessed.ResUlTs After three months of EPA supplementation, the group that received EPA showed significant decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 22 publications
1
32
1
Order By: Relevance
“…Although a few previous studies have reported that n-3 PUFA improved insulin resistance [10], we did not observe any significant improvement in HOMA-R for the EPA group. There are two possible explanations for this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although a few previous studies have reported that n-3 PUFA improved insulin resistance [10], we did not observe any significant improvement in HOMA-R for the EPA group. There are two possible explanations for this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…These actions enforce the beneficial effects on insulin secretion and sensitivity, and glucose homeostasis. However, many previous clinical trials have reported inconsistent results regarding the association of n-3 PUFA intake with the incidence of DM and glycemic control [8–10]. In the present study, we found that EPA treatment resulted in significant improvements in postprandial insulin secretion and glucose homeostasis among patients with IGM and significantly ameliorated the development of DM.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the only randomized controlled trial in the Asian Indian population in the aforementioned meta‐analysis suggested that n ‐3 PUFA could improve glycemic status. Recently, several randomized controlled trials of n ‐3 PUFA supplements among T2D patients have been conducted in Asian countries (from Iran and Japan) . For example, in a randomized double‐blind placebo‐controlled trial among 81 T2D patients in Iran, n ‐3 PUFA supplementation for 2 months significantly decreased HbA1c compared with control group .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded suggesting that before making recommendations for dietary changes or use of food supplements for prevention of diet-related pathologies, is necessary to map a complete picture of the effects of nutrients on many diseases [250]. Several investigations showed that dietary omega-3 FAs may affect glucose metabolism and plasma lipids both in healthy people and patients with metabolic syndrome [251][252][253][254][255][256][257]. Nevertheless, overall the most representative meta-analysis performed in the last decade showed that omega-3 FA supplementation up to 5 g/day consumed for 3 months do not significantly affect insulin sensitivity and glucose homeostasis both in healthy subjects and diabetic patients [258][259][260][261][262].…”
Section: Adverse Effects Of N-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%